1991
DOI: 10.1111/j.1432-1033.1991.tb15795.x
|View full text |Cite
|
Sign up to set email alerts
|

Two functional Na+/K+‐ATPase isoforms in the left ventricle of guinea pig heart

Abstract: Guinea pig left ventricular muscle contains two distinct molecular forms of the N a + /K+-ATPase catalytic a subunit. Sarcolemmal vesicles highly enriched in Na+/K+-ATPase were isolated by a new procedure that yielded specific activities of 60 -100 pmol Pi . h-' . mg-'. SDSjPAGE of isolated sarcolemma after reduction and alkylation of the sulfhydryl groups and identification on immunoblots with specific anti-(a subunit) antibodies indicated the presence of two major polypeptides of 100 kDa and 103 kDa, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…We have reported previously guinea pig ventricular myocytes express two functionally distinct Na/K pumps: one with a high affinity for inhibition by dihydro-ouabain (DHO;* 1 M DHO dissociation constant) and the other with a low affinity (100 M DHO dissociation constant; Gao et al, 1995; for review see Mathias et al, 2000). This is consistent with the observations by others (Mogul et al, 1989;Berrebi-Bertrand et al, 1991). We also have reported that mRNA for the ␣ 1 -and ␣ 2 -isoforms of the Na/K ATPase coexist in guinea pig ventricular myocytes (Gao et al, 1999a).…”
supporting
confidence: 89%
“…We have reported previously guinea pig ventricular myocytes express two functionally distinct Na/K pumps: one with a high affinity for inhibition by dihydro-ouabain (DHO;* 1 M DHO dissociation constant) and the other with a low affinity (100 M DHO dissociation constant; Gao et al, 1995; for review see Mathias et al, 2000). This is consistent with the observations by others (Mogul et al, 1989;Berrebi-Bertrand et al, 1991). We also have reported that mRNA for the ␣ 1 -and ␣ 2 -isoforms of the Na/K ATPase coexist in guinea pig ventricular myocytes (Gao et al, 1999a).…”
supporting
confidence: 89%
“…The role of ␣ 3 Na ؉ /K ؉ ATPase in cough receptor function Sodium pump isozymes can be differentiated by their affinity for ouabain (Maixent et al, 1987;Berrebi-Bertrand et al, 1991;Berrebi-Bertrand and Maixent, 1994;Gao et al, 1995;Juhaszova and Blaustein, 1997;Dobretsov et al, 1999;Lingrel et al, 2003). The apparent potency of ouabain for preventing FM2-10 labeling was consistent with the expression of an ␣ 3 -containing isozyme of Na ϩ /K ϩ ATPase in tracheal cough receptors.…”
mentioning
confidence: 67%
“…Reduction and alkylation of denatured Na+,K+-ATPase has been reported to enhance the electrophoretic separation of the isoforms,34 an observation that we have confirmed for rat brain and heart.32 Reduction and alkylation of guinea pig ventricular Na+,K+-ATPase was reported to cause the a subunit to split into two bands, which were assumed (without more direct evidence) to be al and a2. 33 We attempted to reproduce this. Reduction and alkylation caused an upward shift in the mobility of the Na+,Kt-ATPase a bands as usual ( Fig 10).…”
Section: Other Speciesmentioning
confidence: 99%